IMPLEMENTASI TEAMS GAMES TOURNAMENT MODEL MENINGKATKAN MOTIVASI BELAJAR SISWA DI SD ST. ANTONIUS BANGUN MULIA MEDAN - Pasaribu, Sandiolan Alexsius; Sihotang, Din Oloan (Pastoralia Jurnal Penelitian Dosen, 2024)
This study investigates the effectiveness of implementing the Teams Games Tournament (TGT) model in enhancing students' motivation in the subject of Catholic Education for Grade V B at SD St. Antonius Bangun Mulia Medan during the academic year 2023/2024. The research adopts an action research approach with two cycles, where the first cycle showed students' motivation levels at a "Moderate" level (64%), while the second cycle exhibited a significant increase to a "High" level (82%). The findings reveal that consistently applying the TGT model enhances students' motivation. This motivation improvement is achieved through group interactions and educational games that create an enjoyable and interactive classroom atmosphere. The study recommends schools to implement the TGT model from the beginning of the semester to allow students time to adapt and experience the benefits of this teaching method, thereby sustaining student motivation throughout the learning process.